PENGARUH PARTISIPASI ANGGARAN, REPUTASI DAN ETIKA PADA KESENJANGAN ANGGARAN PADA SKPD DI PEMERINTAHAN KOTA DENPASAR - Damayanti, I Gusti Agung Ayu Putri; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
Budgeting in the public sector is heavily influenced by non-economic factors, in the form of budgetary participation, Reputation, and Ethics. The purpose of this study was to determine the effect of Budget Participation, Reputation, and Ethics In Budget Gaps In Regional Working Units ( on education ) in Denpasar City Government. The population in this study is head of department/head of the agency and head sub section in SKPD in Denpasar City Government amounting to 34 on education. The sample in sampling jenuh. With multiple linear regression analysis, the results of the analysis found that budgetary participation variables, reputation, and ethics affect the budget gap. This suggests that the higher participation and reputation in the preparation of the budget, the higher the budget gap. The higher the lower the ethics budget gaps that occur.
Keywords: budgetary participation, reputation, ethics, and the budgetary slack